A qualitative study of health information-seeking behavior on the Internet among information technology professionals - Priyadarshini Pattath (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: The motivation to seek health information on the Internet for individuals has been varied. The purpose of this paper was to explore the perspectives and experiences about online health information seeking in information technology (IT) professionals. MATERIALS AND METHODS: A qualitative case study research design was employed to examine the behavior of 15 IT professionals from a state organization in the East Coast of the United States of America. Convenience sampling was used to identify the setting, and purposeful sampling was used to select the participants. A survey questionnaire was used as a recruitment tool, and in-depth individual interviews with standardized semi-structured questions were used to collect data. RESULTS: Findings illustrated that the Internet was the first source of reference for wellness and prevention information to maintain a healthy lifestyle, and to alleviate and prevent work-related musculoskeletal disorders (WMSDs). The themes that emerged from the study were that the IT professionals searched the Internet for information to self-educate about medical conditions, to maintain fitness, communicate with health-care professionals, decide their treatment options, and to make lifestyle modifications such as ergonomic adjustment of their workstation, postural adjustments, and changing negative health behaviors. CONCLUSION: The results of this study provide practical implications for organizations and health professionals in providing health education to prevent WMSDs as participants sought health information online to take actions and collaborate with their health-care professionals and actively contributed to their medical health decisions. This underscores a valuable opportunity for health-care providers and public health officials to become more proactive by providing their patients with quality health information outside their office through the Internet by referring them to credible website sources.